2018
DOI: 10.1073/pnas.1716959115
|View full text |Cite
|
Sign up to set email alerts
|

RGMb protects against acute kidney injury by inhibiting tubular cell necroptosis via an MLKL-dependent mechanism

Abstract: Tubular cell necrosis is a key histological feature of acute kidney injury (AKI). Necroptosis is a type of programed necrosis, which is executed by mixed lineage kinase domain-like protein (MLKL) upon its binding to the plasma membrane. Emerging evidence indicates that necroptosis plays a critical role in the development of AKI. However, it is unclear whether renal tubular cells undergo necroptosis in vivo and how the necroptotic pathway is regulated during AKI. Repulsive guidance molecule (RGM)-b is a member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 63 publications
0
58
1
Order By: Relevance
“…As global RGMb -deficient mice die in the early postnatal stage, only heterozygous mice or tubular cell-specific knockout mice are used to study AKI. Employing the latter approach, Liu et al [25] demonstrated an aggravation of post-ischemic AKI or acute oxalate nephropathy, which confirms RGMb as an endogenous inhibitor of tubular injury (Table 1). Elegant in vitro studies demonstrate that lack of RGMb enhances MLKL deposition in tubular cell membranes and the execution of renal cell death.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 85%
See 1 more Smart Citation
“…As global RGMb -deficient mice die in the early postnatal stage, only heterozygous mice or tubular cell-specific knockout mice are used to study AKI. Employing the latter approach, Liu et al [25] demonstrated an aggravation of post-ischemic AKI or acute oxalate nephropathy, which confirms RGMb as an endogenous inhibitor of tubular injury (Table 1). Elegant in vitro studies demonstrate that lack of RGMb enhances MLKL deposition in tubular cell membranes and the execution of renal cell death.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 85%
“…RGMb has diverse biological functions that relate to its modulatory effect on IL-6 expression and neurite outgrowth but it was recently described as an inhibitor of MLKL homotrimer binding to the plasma membrane, and hence as another endogenous necroptosis inhibitor [25]. Interestingly, RGMb is highly expressed in tubular epithelial cells.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
“…Necroptosis is also involved in kidney diseases. RIPK3 and MLKL are activated during acute kidney injury, where MLKL is expressed on the apical membrane of proximal tubules [85]. Thus, this suggests that the necrosome is an active mediator of kidney injury.…”
Section: Necroptosis In Kidney Injurymentioning
confidence: 99%
“…A recent study showed that conditional knockout of repulsive guidance molecule (RGM)b, a member of the RGM family, induced MLKL expression at the apical membrane and increased renal dysfunction. These findings indicate that RGMb prevents AKI by inhibiting MLKL membrane association and necroptosis in tubular epithelial cells (17,19). However, the regulatory mechanism of MLKL signaling is unknown, and targeted therapy is lacking.…”
Section: Discussionmentioning
confidence: 97%